EXCELLENCE PERFORMANCE OF THE BANKING SERVICE ACCORDING TO THE ELECTRONIC MANAGEMENT APPLIED RESEARCH IN A SAMPLE OF PRIVATE BANKS - Nibras Jasim Kadhim, Shaymaa Mahdi Kadhim (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The current research aims to shed light on the role of electronic management requirements in achieving the Excellence banking performance of the research community represented by (Middle East Investment and Finance Bank, Al-Watani Islamic Bank, Bank of Baghdad) to identify the trends and opinions of its employees, which included (the board of directors, the managing director, the deputy director commissioner and managers Departments, divisions, and units), especially since most banking institutions do not have a clear vision in this area, and the research method has been applied as a case study of the accuracy of the data that will be used in the current research, which was collected through personal interviews of officials supported by a checklist to produce a set of results. And the proposals that contribute to raising the performance of banking institutions, and the research presented a set of results, the most important of which was that there was a discrepancy in the results of the requirements of electronic management, since despite the availability of high technology, most departments suffer from the lack of qualified human cadres to work in electronic work, as the size of the gap reached (40) %), Which is a very high percentage, as well as that banking institutions own a significant percentage of financial capabilities that allow them to switch to electronic work Most of the research sample has reservations about this because of hacking and electronic piracy.